Tinjauan Hukum Islam Tentang Pasal 88 UU No. 6 Tahun 2023 Tentang Cipta Kerja Terhadap Tanggung Jawab Suami Dalam Keluarga - Revananza Razavi Setiawan; Sofia Gussevi; Azi Ahmad Tadjudin (al-Battar: Jurnal Pamungkas Hukum, 2025)
This study aims to describe how the role of Islamic law in reviewing the Job Creation Law has an impact on the husband's responsibility towards his family. This is the basis for why the theme was chosen as the object of research. The method used in this study is descriptive qualitative. The data collection technique used in this study is Library Research. Where research data is collected from various studies, journals, fiqh books to comparative analysis between one law and another. Based on the findings, several factors and impacts were found due to the enactment of the Job Creation Law. Based on the results of the data analysis, several concepts of the Job Creation Law were found related to wage provisions. First, according to article 88C, the amount of the minimum wage is determined by the Governor. Second, according to article 88B, wages are obtained based on units of time and results. Third, the nominal amount of the minimum wage obtained by workers, if referring to article 88C as the wage is determined by the Governor, then the determination of the wage is based on considerations of economic conditions, inflation and certain indices. This policy is stated in the next article, namely article 88D. If we look at it from the perspective of Islamic law, then the provisions of wages use the theory of ijarah, in which all the terms and conditions must be met. Starting from the contract, the terms and conditions, as well as things that can cancel the ijarah itself.